Penerapan Metode Fun Learning untuk Menghafal Kosakata Bahasa Arab Siswa di Roudlotut Tholibin Kota Metro - Oktafia, Anita; Fadilah, Fitria Nurul; Zainuddin, Ammar (Al Maghazi : Arabic Language in Higher Education, 2023)
The grade two students at SD Al-Qur'an Roudlotut Tholibin have difficulty remembering vocabulary in the process of learning Arabic. Because they consider that learning Arabic was a difficult thing to do because it’s a foreign language. However, using fun method did not bored and easier for students to capture the material or vocabulary that has been given. The article was conducted to determine the application of fun learning methods in grade 2 students at SD Al-Qur'an Roudlout Tholibin in learning Arabic to make it easier for students to memorize Arabic vocabulary. The type of research is descriptive qualitative research, where the data collection used interview, observation and documentation methods. In the from observations result found that the main problem was that students had difficulty understanding Arabic words hence it affected when students memorized vocabulary. In order for students to easily capture the material provided by the teacher, the right method was needed. Therefore, the Fun Learning method was considered to have a positive influence on the teaching and learning process of Arabic because it’s focuses on creating an interactive and comfortable learning atmosphere. Hence, the children did not bored and running well. For example, providing vocabulary material through singing or through games, that way students wmore easily capture the material delivered by the teacher. Keywords: Fun Learning Method, Arabic Vocabulary, Memorizing Vocabulary